The relation between snatch and exclusive power in wrestling - فرحان التميمي, أحمد (Journal of Physical Education, 2019)
The aim of this study knows the relation between snatch and exclusive power in wrestling to sample of sixteen youth wrestlers (20-18) years old from police club .the forager using depiction style to reach to goal of this study. The final results are the exclusive power to measles of arms, legs, abdomen, back was very important in this study.